2022
DOI: 10.1115/1.4056113
|View full text |Cite
|
Sign up to set email alerts
|

Effective Constitutive Relations for Sintered Nano Copper Joints

Abstract: Sintered copper nano particles are being considered as alternatives to solder and/or sintered silver in different applications. Like for the alternatives, interpretation of accelerated fatigue test results does however require modeling, typically involving prediction of stresses and strains vs. time and temperature based on constitutive relations. This poses a challenge as the inelastic deformation properties depend strongly on both the initial particles and details of the processing, i.e. unlike for solder ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Work done by Thekkut et al showed densified Cu-on-Cu bonds of nanoparticulate paste (Showa Denko Materials Co. Ltd., Tokyo, Japan/former Hitachi Chemical Co Ltd.) after 1 h of sintering at 300 °C in forming gas (FG) environment under 20 MPa pressure. 27,30 A similar study was also done by Liu et al whereby Cu-on-Cu bonds were formed by sintering of Cu nanoparticles that were pretreated with formic acid. 31 As seen in Figure 2, the sintered joints feature porosity due to the evaporation and partial evacuation of organic binding material during sintering, that leads to inferior mechanical properties.…”
Section: New Trendsmentioning
confidence: 66%
See 4 more Smart Citations
“…Work done by Thekkut et al showed densified Cu-on-Cu bonds of nanoparticulate paste (Showa Denko Materials Co. Ltd., Tokyo, Japan/former Hitachi Chemical Co Ltd.) after 1 h of sintering at 300 °C in forming gas (FG) environment under 20 MPa pressure. 27,30 A similar study was also done by Liu et al whereby Cu-on-Cu bonds were formed by sintering of Cu nanoparticles that were pretreated with formic acid. 31 As seen in Figure 2, the sintered joints feature porosity due to the evaporation and partial evacuation of organic binding material during sintering, that leads to inferior mechanical properties.…”
Section: New Trendsmentioning
confidence: 66%
“…In recent years, nanomaterials have increasingly gained interest as next generation interconnects in electronic packaging. Nanomaterials have shown promising potential as the next generation solder materials for interconnection below 20 μm in ultrafine pitch assembly. , Sintering of nano-Cu pillars or nanoporous (np) Cu caps have shown potential to realize a direct Cu–Cu bonding. , It is known that nanostructured metals have high surface area-to-volume ratio which significantly lowers their melting temperature in comparison with their bulk counterparts . This makes them particularly attractive for low-temperature sintering.…”
Section: New Trendsmentioning
confidence: 99%
See 3 more Smart Citations